2014
DOI: 10.5812/aapm.19529
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic Acid Interaction With Analgesic Effect of Morphine and Tramadol in Mice

Abstract: Background:Combining different analgesic drugs for improvement of drug efficacy is a recommended strategy intended to achieve the optimal therapeutic effects.Objectives:The purpose of the present study was to assess the nature of the interaction between ascorbic acid and two analgesic drugs, morphine and tramadol.Materials and Methods:The analgesic activity was assessed by the acetic acid writhing test in male Naval Medical Research Institute (NMRI) mice. The results were obtained using four to six animals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Combining tramadol or morphine with other drugs can decrease the high postoperative dosages of administered opiates and thus, can lead to less drug adverse effects ( 4 , 36 ). Several studies have suggested ways to manage postoperative pain after arthroscopy, some of which are IA injection of different drugs combination.…”
Section: Discussionmentioning
confidence: 99%
“…Combining tramadol or morphine with other drugs can decrease the high postoperative dosages of administered opiates and thus, can lead to less drug adverse effects ( 4 , 36 ). Several studies have suggested ways to manage postoperative pain after arthroscopy, some of which are IA injection of different drugs combination.…”
Section: Discussionmentioning
confidence: 99%
“…Two case reports and a cohort study from Schencking et al described clinical improvement and relief of pain for patients with acute herpes zoster exacerbation who received L-ascorbic acid [27,28]. Double-blind placebo-controlled study revealed that the duration of pain caused by labial herpes was shortened by 51%, when patients were administered 1 g/day of L-ascorbic acid together with bioflavonoids [29]. Ascorbate treatment also resulted in a better efficacy than placebo in pain modulation in post herpetic neuralgia (PHN) and intravenous ascorbate helps relieve spontaneous pain in PHN [30,31].…”
Section: Comments Potential Mechanism Of Actionmentioning
confidence: 99%
“…Combination of vitamin C supplements with aspirin and opiates has a strong synergistic effect on these drugs [54,74]. On the other hand, oral contraceptive pills increases ascorbic acid turnover and reduce level of ascorbic acid [75].…”
Section: Vitamin C and Drug Absorptionmentioning
confidence: 99%